Kondo effect and RKKY interaction assisted by magnetic anisotropy in a frustrated magnetic molecular device at zero and finite temperature. Issue 10 (4th March 2021) - Nan, Nan; Li, Wei; Wang, Peng-Chao; Hu, Yong-Jin; Tan, Guo-Long; Xiong, Yong-Chen
Abstract : We consider a magnetic molecular trimer sandwiched between two metal electrodes, and study the effect of magnetic anisotropy on the charge transport properties, the Kondo effect, and the temperature and inter-monomer hopping robustness. Abstract : Molecular magnetic compounds, which combine the advantages of nanoscale behaviors with the properties of bulk magnetic materials, are particularly attractive in the fields of high-density information storage and quantum computing. Before molecular electronic devices can be fabricated, a crucial task is the measurement and understanding of the transport behaviors. Herein, we consider a magnetic molecular trimer sandwiched between two metal electrodes, and, with the aid of the sophisticated full density matrix numerical renormalization group (FDM-NRG) technique, we study the effect of magnetic anisotropy on the charge transport properties, illustrated by the local density of states (LDOS, which is proportional to the differential conductance), the Kondo effect, and the temperature and inter-monomer hopping robustness. Three kinds of energy peaks are clarified in the LDOS: the Coulomb, the Kondo and the Ruderman–Kittel–Kasuya–Yosida (RKKY) peaks. The local magnetic moment and entropy go through four different regimes as the temperature decreases. The Kondo temperature T K could be described by a generalized Haldane's formula, revealing in detail the process where the local moment is partially screened by the itinerant electrons. A relationship between the width of the Kondo resonant peak W K and T K is built, ensuring the extraction of T K from W K in an efficient way. As the inter-monomer hopping integral varies, the ground state of the trimer changes from a spin quadruplet to a magnetically frustrated phase, then to an orbital spin singlet through two first order quantum phase transitions. In the first two phases, the Kondo peak in the transmission coefficient reaches its unitary limit, while in the orbital spin singlet, it is totally suppressed. We demonstrate that magnetic anisotropy may also induce the Kondo effect, even without Coulomb repulsion, hence it is replaceable in the many-body behaviours at low temperature.